The impact of COVID-19 on research within the homeless services sector. Issue 3 (7th December 2021) - Waegemakers Schiff, Jeannette; Weissman, Eric Paul; Scharf, Deborah; Schiff, Rebecca; Campbell, Stephanie; Knapp, Jordan; Jones, Alana
Abstract : Purpose: This paper aims to discuss the challenges of conducting research with homelessness services frontline workers during the COVID-19 pandemic. Design/methodology/approach: Between 2015 and 2019, the research team surveyed frontline staff in three cities about their psychosocial stressors and needs. In 2020, the authors replicated the previous study and expanded data collection to seven cities across Canada to determine the extent to which the COVID-19 pandemic impacted the well-being of frontline staff. This report describes how the authors adapted the research methodologies to continue work throughout the pandemic, despite various restrictions. Findings: The original studies had very high participation rates because of several methodological approaches that minimized barriers, especially in-person data collection. During the pandemic, distancing requirements precluded replication of these same methods. Research strategies that enabled staff participation during working hours, with designated time allotted for participation, was key for ensuring high participation rates, as access to technology, availability of free time and other factors frequently make online survey research a hardship for these staff. Restrictive interpretation and regional variations of COVID-19 guidelines by some research ethics boards were also a challenge to rapid and responsive data collection. Originality/value: Few studies describe the experiences of frontline workers in the homelessness sector, and quantitative reports of their experiences are particularly scant. Consequently, little is known about specific methodologies that facilitate large-scale data collection in the homelessness services sector. The present research advances the field by providing lessons learned about best practice approaches in pre and post COVID-19 front line worker contexts. A strength of this research is the well-controlled design. The authors collected data within several of the organizations that had previously participated. This fortunate baseline provided opportunity for comparison before and during the pandemic; the authors can highlight factors that might have had influence during the pandemic.